3D Display for 3D Telepresence: A Review (International Journal of Innovative Computing, 2021)
Over the years, people have tried to advance 3D display technology and researchers as well as developers have created different innovations in recent decades. there are many other different types of 3D display technology that can be classified into stereoscopic, auto stereoscopic, holographic and volumetric 3D displays. This paper, however, discusses the 3D display technology that have been implemented in the telepresence system, which can be divided into two main devices, projectors and head mounted display (HMD). From these two devices, the 3D display technology using projector devices are on-stage hologram, auto stereoscopic display, and holographic projection; while for HMD can be divided into MR headset and VR HMD. This paper provides a review on these 3D display for telepresence. Finally, we make a comparison based on the features of the 3D display technologies such as life-size capability, viewable from different perspectives, headset-free experience number of viewers per device, level of ease of setup and the nausea of discomfort level. To choose the best 3D display technology for a telepresence system, we must first identify the number of users who will be projected and who will be viewed. The goal and activity of using telepresence technology will also define the appropriate type of 3D display.
Keywords: Telepresence, 3D Display, Holographic Projection, Mixed Reality, Virtual Reality